Cinta Beda Agama dalam Bingkai Moderasi Beragama: Antara Realitas Sosial dan Nilai Keberagaman (International Forum of Researchers and Lecturers, 2025)
This research examines the issue of interfaith marriage in the context of religious moderation in Indonesia. This research uses a qualitative method with a library research approach. Based on Dukcapil data from 2022, 34.6 million couples were recorded as